The Role of Instrumental and Expressive Social Ties in Employees' Perceptions of Organizational Justice - Umphress, Elizabeth Eve; Labianca, Giuseppe (Joe); Brass, Daniel J.; Kass, Edward (Eli); Scholten, Lotte (Organization Science, 2003)
We argue that employees' organizational justice perceptions are, in part, influenced by whom they associate with in the workplace. Consequently, we examine the link between different types of social ties and the interpersonal similarity of employees' perceptions of interactional, procedural, and distributive justice through a social network study in a division of a Fortune 500 firm. We predicted and found that social ties influence perceptions of justice to different extents, depending on the type of justice assessed. Expressive ties were associated with greater similarity in coworkers' perceptions than instrumental ties in the most affect-inducing justice perceptions, perceptions of interactional justice. Our findings suggest that the opinions held by an individual's coworkers influence others' justice perceptions, especially when justice is ambiguous and affect inducing, and that different justice perceptions may be transmitted via different types of social ties.